ABNORMAL FLOW PATTERN AND GEOMETRY ARE INTERRELATED AND CONTRIBUTE TO PROXIMAL DESCENDING AORTA DILATION IN MARFAN PATIENTS: A 4D FLOW MRI STUDY. (June 2018) - Guala, A.; Dux-Santoy, L.; Ruiz-Muñoz, A.; Rodriguez-Palomares, J.; Maldonado, G.; Villalva, N.; Fernandez, R.; Valente, F.; Gutierrez, L.; Galian, L.; Garcia-Dorado, D.; Evangelista, A.; et al.
Abstract : Objective: Marfan syndrome (MFS) is a hereditary connective tissue disorder caused by mutation in the FBN1 gene. Diseases of the ascending aorta (AAo), like dilation or type A dissection, are very prevalent. However, after improvements in the surgical AAo management, diseases of the descending aorta (DAo) emerged as a clinical issue. Recent qualitative studies in MFS have revealed the existence of abnormal vortex in the proximal DAo which were related to local dilation. However, any study has investigated the origin of these vortices. The aim of the present investigation was to investigate the relationship between aortic geometry and abnormal flow characteristics in the thoracic aorta of MFS Figure. No caption available. Design and method: Fifty-tree confirmed MFS patients without congenital heart diseases or aortic valve disease were prospectively included from our Aortic unit. Also, 40 age-matched healthy volunteers (HV) were recruited. All participants underwent non-contrast-enhanced 4D flow-MRI, obtaining flow field and angiography. Geometric parameters (diameter, ellipticity and curvature) and rotational flow characteristics (in-plane rotational flow IRF, systolic flow reversal ratio SFRR) were evaluated (see figure 1) at 20 planes through the thoracic aorta. Results: Aortic diameters were significantly-larger in MFS in the proximal AAo (p < 0.001) and in the proximal DAo (p = 0.028) compared to HV, while no differences were found in the remaining region. Ellipticity was increased and peak of aortic curvature was larger and more distal in MFS compared to controls (figure 2) Rotational flow (IRF, related to helicity) was reduced in MFS patients in the majority of the thoracic aorta, while SFRR (backward systolic flow) was increased in the proximal AAo and DAo. Bivariate correlation showed inverse relation between arch ellipticity (R = −0.34, p = 0.016) as well as proximal DAo peak curvature (R = −0.35, p = 0.015) and arch IRF. Maximum proximal DAo diameter was negatively correlated with local IRF (R = −0.3, p = 0.038) and positively correlated with local SFRR (R = 0.605, p < 0.001). Conclusions: Abnormal aortic ellipticity and curvature were evident in MFS patients and related to a reduction of flow helicity and increase of vorticity in the DAo. Longitudinal studies are needed to investigate eventual prognostic value of aortic geometry and flow in MFS patients.